2011
DOI: 10.1002/biot.201100013
|View full text |Cite
|
Sign up to set email alerts
|

ApoTome to visualize E‐cadherin and p63 expression in oral pre‐cancer

Abstract: Precise histopathological localization of E-cadherin and p63 is of immense importance in understanding the integrity of oral mucosal stratified epithelium in normal and diseased conditions. Necessarily immunohistochemical imaging should have minimum bleaching impact on the dyes and ability to produce clear and crisp images. Here ApoTome provides an alternative with metal halide light source and structured illumination under the assistance of grids, along with integrated image processing modality to generate cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…These areas represent subareas of AGm and mFC, which prevented us from confounding our counts with cells from neighboring areas. The entire extent of a 50 μm slice was then imaged at 2 μm intervals using Zeiss Apotome technology to precisely localize cells 30 and the resulting data was reconstructed in 3 dimensions using Imaris (Bitplane) imaging software to create a 60 mm 3 volume obtained in an unbiased manner (please see supplementary figures). Such volumes were taken from each animal both ipsilesional and contralesional to the stroke.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas represent subareas of AGm and mFC, which prevented us from confounding our counts with cells from neighboring areas. The entire extent of a 50 μm slice was then imaged at 2 μm intervals using Zeiss Apotome technology to precisely localize cells 30 and the resulting data was reconstructed in 3 dimensions using Imaris (Bitplane) imaging software to create a 60 mm 3 volume obtained in an unbiased manner (please see supplementary figures). Such volumes were taken from each animal both ipsilesional and contralesional to the stroke.…”
Section: Methodsmentioning
confidence: 99%
“…The entire anterior-posterior extent of the CFA stroke was analyzed and sections representing the largest medial-lateral area were imaged (thus representing the central core and largest area of stroke damage). The entire extent of 50 μm slices were then imaged at 2 μm intervals using Zeiss Apotome technology to precisely localize puncta 30 and the resulting data was reconstructed in 3 dimensions using Imaris (Bitplane) imaging software. An investigator blinded to the experimental condition counted the number of Fluoro-Jade C positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…Knock down of ENO1 downregulated the activation of pRB, oncogenic cell cycle regulator like cyclin D1, E1 and NF-κβ 28. Our previous study also reported the emergence of EMT attributes (increased cytoplasmic expression of E-cadherin and β-catenin; upregulated gene expression of TWIST1, ZEB1 and MMP9) in OSFWD 42. However, none of them emerges as definite molecular marker with precise clinical value for oral precancer like OSF.…”
Section: Discussionmentioning
confidence: 79%
“…The poor quality of images obtained by conventional wide-field fluorescence microscopy is due to out-of-focus light; spheres located throughout the matrix are illuminated, therefore those above or below the imaging plane appear highly blurred. Structured illumination using ApoTome technology fitted on a conventional wide-field fluorescence microscope enables researchers to obtain images with similar resolution to confocal microscopy (9). The principle is based on projecting a grid onto the in-focus plane of the sample and acquiring at least three raw images with the grid in three different positions in order to identify in-focus areas (10).…”
Section: Introductionmentioning
confidence: 99%